Prevalence, serovar, and antimicrobial resistance of Salmonella isolated from meat and minced meat used for production smoked sausage. Issue 1 (October 2021) - Zaiko, E V; Bataeva, D S; Yushina, Yu K; Grudistova, M A; Velebit, B
Abstract: The objective of this study was to research the prevalence, serovars, and antimicrobial resistance profiles of Salmonella isolated from meat and minced meat used for the production of fermented sausage. A total of 116 samples were tested, and among them, 20 (17.2%) were positive. Salmonella was detected in 3 (10.3%) beef samples, 5 (19.2%) pork samples, and 6 (20.7%) poultry samples. In minced meat, the Salmonella prevalence was 18.8%. Salmonella enterica serovar Agama (5.2%) was the most commonly identified serovar, followed by S. Enteritidis (4.3%), S . Typhimurium (3.4%), S. Infantis (2.6%), and S. Lindenburg (1.7%). Most of the serovars identified in the present study are recognized as frequent causes of human salmonellosis. Thus, the presence of these serovars means foods with these meats are a likely source of human infections. We found the Salmonella isolates exhibited high rates of resistance to antimicrobials tetracycline, ampicillin, streptomycin, and ciprofloxacin. The highest level of resistance was to tetracycline (75%), followed by resistance to ampicillin (50%), streptomycin (30%), ciprofloxacin (20%), gentamicin (20%), and neomycin (10%). The high-level resistance observed for some of the serovars calls for concern. Salmonella with multidrug resistance in meat used to produce fermented sausages is considered a high additional risk for human health.